2013
DOI: 10.1017/s1742758413000374
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of no-choice cage, detached leaf and diet incorporation assays to screen chickpeas for resistance to the beet armyworm Spodoptera exigua (Lepidoptera: Noctuidae)

Abstract: It is difficult to compare genotypic resistance to insects across seasons and locations because of the variation in the onset and severity of insect infestation. Therefore, in this study, we used the no-choice cage technique and detached leaf and artificial diet incorporation assays for evaluating chickpea genotypes for resistance to the beet armyworm Spodoptera exigua (Hubner). The results indicated that the no-choice cage technique was not useful for evaluating chickpea genotypes for resistance to S. exigua.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Heavy rains in the 2010-11 post-rainy season possibly washed out the organic acids on the chickpea leaves (Sharma et al, 2010), resulting in reduced differences in leaf feeding and larval survival between the genotypes tested. Lower leaf feeding, larval survival and larval mass gain were recorded on EC 583260, EC 583264 and ICC 12475 (Shankar et al, 2014). Narayanamma et al, 2007 reported low larval survival and mass gain on ICC 12475.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Heavy rains in the 2010-11 post-rainy season possibly washed out the organic acids on the chickpea leaves (Sharma et al, 2010), resulting in reduced differences in leaf feeding and larval survival between the genotypes tested. Lower leaf feeding, larval survival and larval mass gain were recorded on EC 583260, EC 583264 and ICC 12475 (Shankar et al, 2014). Narayanamma et al, 2007 reported low larval survival and mass gain on ICC 12475.…”
Section: Discussionmentioning
confidence: 93%
“…The test genotypes, ICCL 86111 and ICC 3137, which had shown resistant and susceptible reaction under field conditions, respectively (Shankar et al, 2013), were grown under field and greenhouse conditions at the International Crops Research Institute for the Semi-Arid Tropics (ICRISAT), Patancheru, Telangana, India (latitude 17.53 0 N, longitude 78.27 0 E and an altitude of 545 m).…”
Section: Methodsmentioning
confidence: 99%
“…In India, the beet armyworm inflicts damage on a wide range of crops such as cotton, castor bean, spinach, tomato, cabbage, chillies, and alfalfa. Occasionally, outbreaks of this pest lead to substantial economic losses in various economically important crops across India 4 7 . Availability of host plants of both highly suitable and less suitable or non-suitable host plants can influence the S. exigua spatio-temporal population dynamics, density, spread, and distribution pattern in the agricultural landscape 7 , 8 .…”
Section: Introductionmentioning
confidence: 99%
“…(barrel medic), have been shown to lose their resistance against aphids when excised tissues were used (Klingler et al., ; Liu & McCreight, ). Nevertheless, the excised leaf assay is a simple and convenient method, and is still used in some research; however, the reason for the altered resistance to aphids after leaf detachment remains largely unknown (Shankar et al., ; Stobbs et al., ).…”
Section: Introductionmentioning
confidence: 99%